The Finnish pension reform of 2005 - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2006)
A major reform in the Finnish private-sector earnings-related pension system came into effect on January 1st, 2005. It was negotiated in 2001 – 2002 between the central organisations of employers and trade unions and representatives of the central government. This paper describes the reform and analyses its effects on selected macroeconomic variables, on the pension system and on the position of different birth cohorts and different educational groups. The reform appears to be successful in many respects. It simplifies the private-sector pension system and makes it a model that other pension systems in Finland will converge to. The reform rewards postponing retirement. It curbs the increase in contribution rate without endangering the adequacy of replacement rates. The increase in labour supply will have beneficial welfare effects. The new system also responds rather well to uncertain future demographics. Despite this apparent success of the reform there remains a serious doubt of its adequacy, as contribution rates are still expected to rise by several percentage points.
Keywords: H55; J11; 330; pension reform; population ageing; stochastic population simulations; Rentenreform; Alterssicherung; Bevölkerungsentwicklung; Private Rentenversicherung; Simulation; Finnland